48(2x-1)=8(x+5)+2x

Simple and best practice solution for 48(2x-1)=8(x+5)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 48(2x-1)=8(x+5)+2x equation:


Simplifying
48(2x + -1) = 8(x + 5) + 2x

Reorder the terms:
48(-1 + 2x) = 8(x + 5) + 2x
(-1 * 48 + 2x * 48) = 8(x + 5) + 2x
(-48 + 96x) = 8(x + 5) + 2x

Reorder the terms:
-48 + 96x = 8(5 + x) + 2x
-48 + 96x = (5 * 8 + x * 8) + 2x
-48 + 96x = (40 + 8x) + 2x

Combine like terms: 8x + 2x = 10x
-48 + 96x = 40 + 10x

Solving
-48 + 96x = 40 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-48 + 96x + -10x = 40 + 10x + -10x

Combine like terms: 96x + -10x = 86x
-48 + 86x = 40 + 10x + -10x

Combine like terms: 10x + -10x = 0
-48 + 86x = 40 + 0
-48 + 86x = 40

Add '48' to each side of the equation.
-48 + 48 + 86x = 40 + 48

Combine like terms: -48 + 48 = 0
0 + 86x = 40 + 48
86x = 40 + 48

Combine like terms: 40 + 48 = 88
86x = 88

Divide each side by '86'.
x = 1.023255814

Simplifying
x = 1.023255814

See similar equations:

| 2x-7+3x=4x+2 | | 2x-7+3x=4x+2x | | 7a^2-6=0 | | -3x+1=-6x-4 | | (16x+9)-4x= | | 16-3(x+1)=x-3 | | -15b=10 | | y(-8)=-72 | | X=-3+2x | | 8a=2 | | b+8=-14 | | 13r+3r^2=10 | | n-3(3n-3)=33 | | X+12=2x+9 | | -10+13r+3r^2=10 | | 24-2x=-2x | | 2(+z)+1=11-4z+6z | | 10+3(4-6a)=-(6a+12) | | y+18-18=39 | | 2n+6=28 | | 4v^2-5v-6=0 | | 3(5+10x)-12(4+2x)= | | 4x+6-3y=22x+4 | | -36+5v=5v+6(3v-3) | | (x-1)(x+3)-12=0 | | -36-2x=-8x+4(x-8) | | -4x-3=3x-9 | | 4(x+2)=3(x+9) | | -(-8-8k)+1=15+8k | | 5n+5=40 | | 2(4x-3)+4=5x-6 | | -33+7m=5(m-1)-5m |

Equations solver categories